Familial colorectal cancer: Patient assessment, surveillance and surgical management. Issue 2 (February 2017) - Kennelly, R.P.; Gryfe, R.; Winter, D.C.
Abstract: Germline mutations account for 5–10% of colorectal cancer. Most mutations are autosomal dominant with high penetrance and affected patients benefit greatly from appropriate treatment. This review presents the current knowledge regarding familial colorectal cancer and provides practical information based on international guidelines and the best available evidence regarding patient assessment, surveillance and surgical management. Surgeons are often the first point of contact and frequently, the main provider of care for families with cancer syndromes or patients with familial cancer. Patients with a polyposis phenotype should undergo appropriate genetic testing. In non-polyposis patients with a cancer diagnosis, tumor testing for Lynch syndrome can guide the use of genetic testing. In patients without a personal history of cancer or polyposis, a carefully obtained family history with testing of available tumor tissue or of a living relative affected by colorectal cancer informs the need for genetic testing. Surveillance and surgical management should be planned following thorough assessment of familial cancer risk. Evidence exists to provide guidance as to the surveillance strategies required, the specific indications of genetic testing and the appropriate timing of operative intervention. A carefully obtained family history with selective genetic testing should inform surveillance and surgical management in patients who have a genetic predisposition for the development of colorectal cancer.